COVID-19 Staff Wellbeing Survey: longitudinal survey of psychological well-being among health and social care staff in Northern Ireland during the COVID-19 pandemic - Julie-Ann Jordan; Ciaran Shannon; Dympna Browne; Emma Carroll; Jennifer Maguire; Keith Kerrigan; Sinead Hannan; Thomas McCarthy; Mark A. Tully; Ciaran Mulholland; Kevin F. W. Dyer (BJPsych Open, 2021)
Background Throughout the coronavirus disease 2019 (COVID-19) pandemic, health and social care workers have faced unprecedented professional demands, all of which are likely to have placed considerable strain on their psychological well-being.